2014
DOI: 10.1111/bcp.12263
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of intravenous and inhaled fluticasone furoate in healthy Caucasian and East Asian subjects

Abstract: AimThe aim of the study was to evaluate the pharmacokinetics (PK) of inhaled and intravenous (i.v.) fluticasone furoate (FF) in healthy Caucasian, Chinese, Japanese and Korean subjects.MethodThis was an open label, randomized, two way crossover study in healthy Caucasian, Chinese, Japanese and Korean subjects (n = 20 per group). Inhaled FF (200 μg for 7 days, then 800 μg for 7 days from a dry powder inhaler [DPI]) was administered in one treatment period and i.v.FF (250 μg infusion) in the other. FF PK and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 17 publications
7
25
1
Order By: Relevance
“…However, the PK characteristics of FF and UMEC have been extensively studied, and the data presented here are broadly consistent with these studies; in healthy volunteers, repeat-dose inhaled FF 200 mcg and 800 mcg had a plasma t max of 30-45 min (similar to the t max of 30 min reported here) and a t of 25.5-32.5 h [25].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the PK characteristics of FF and UMEC have been extensively studied, and the data presented here are broadly consistent with these studies; in healthy volunteers, repeat-dose inhaled FF 200 mcg and 800 mcg had a plasma t max of 30-45 min (similar to the t max of 30 min reported here) and a t of 25.5-32.5 h [25].…”
Section: Discussionsupporting
confidence: 85%
“…A previous study has demonstrated higher FF systemic exposure following inhaled dosing in East Asian subjects compared with Caucasian subjects[25], although this was not associated with a clinically significant effect on serum cortisol, and therefore dose adjustment in East Asian subjects was deemed unnecessary. However, there were insufficient data to draw conclusions regarding differences in systemic exposure between AfricanAmerican/African and Caucasian subjects in the present study.…”
mentioning
confidence: 91%
“…Systemic exposure to fluticasone furoate after inhalation was modestly (\50 %) higher in healthy East Asian (Chinese, Korean and Japanese) subjects than in healthy Caucasians [31]. However, the increased exposure was not associated with a clinically significant effect on serum cortisol; therefore, dose adjustment is not required in East Asian subjects [31].…”
Section: In Special Patient Populationsmentioning
confidence: 97%
“…However, the increased exposure was not associated with a clinically significant effect on serum cortisol; therefore, dose adjustment is not required in East Asian subjects [31]. Similar results are reported for fluticasone furoate in East Asian, Japanese and South East Asian patients with asthma; in these patients, vilanterol C max is predicted to be 220-287 % higher than in other racial groups, with no evidence of clinically significant effect on heart rate because of the higher C max [2].…”
Section: In Special Patient Populationsmentioning
confidence: 99%
“…• Smaller lungs and smaller airways in Asians were discussed to influence fluticasone furoate PK after inhalation [42] Sex (male, female)…”
Section: Figurementioning
confidence: 99%